2000
DOI: 10.1053/rmed.1999.0731
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of endobronchial metastases with intraluminal radiotherapy

Abstract: Metastasis to the lung occurs quite commonly from certain types of extrapulmonary primary carcinoma. Spread to the bronchial lumen is relatively rare. When this does occur, symptoms resembling those of primary bronchial carcinoma are often present, in association with partial or complete obstruction of the bronchial lumen. Palliation of such symptoms is possible with the use of intraluminal radiotherapy (ILT). Between 1990 and 1998, 37 patients with endobronchial metastases were treated using this modality; a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Intraluminal radiotherapy is one of the treatment choices for the palliation of symptoms [21][22][23]. However, its effect on survival time has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal radiotherapy is one of the treatment choices for the palliation of symptoms [21][22][23]. However, its effect on survival time has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Sørensen et al found that around two-thirds of patients benefited symptomatically from ILT 10. This offers a distinct advantage over external beam therapy as it can deliver high-dose radiation to a localised area with significantly less side effects, especially when the patient already has a decreased cardiac or pulmonary functional status 11…”
Section: Discussionmentioning
confidence: 99%
“…The presence of endobronchial metastases usually implies a poor prognosis. 9 Endobronchial metastases in FTC can develop via several mechanisms. It has been hypothesized that bronchial lesions can occur due to direct invasion of parenchymal lesion, direct extension of mediastinal lesions, transbronchial aspiration, direct lymphatic spread, and/or direct metastasis via the bronchial artery.…”
Section: Discussionmentioning
confidence: 99%